Differences in the recovery response from high-intensity and high-volume resistance exercise on force, reactive agility, and cognitive function - Tavor Ben-Zeev; Bar Reisfeld; Aviad Mashiach; Jay R Hoffman (Termedia Publishing House, 2024)
Purpose This study compared the recovery response of physical performance and cognitive function between high volume, low intensity (HV) and high intensity, low volume (HI) resistance training in resistance trained men. Methods Eight recreationally resistance trained men (27.8 ± 1.6 y; 85.5 ± 11.2 kg; 178.4 ± 8.3 cm), with at least one-year of resistance training experience (6.4 ± 3.9 y) participated in this cross-over design study. Participants were randomly assigned to either HV (6-sets of 15-20 repetitions at 60% of the participant's one-repetition maximum (1RM), 1-min rest between sets) or HI (6-sets of 3-5 repetitions at 90% 1RM, 3-min rest between sets). Following a one-week recovery period, participants reported back to the laboratory and performed the other training session. Cognitive function (SCAT5), physical performance (isometric mid-thigh pull), and reactive agility measures were assessed at baseline, immediately-post (IP) and at 30- (30P) and 60-minutes post-exercise. Results Parametric analysis revealed no differences in peak force (p = 0.423), and the rate of force development at 200 ms (p = 0.827) and 250 ms (p = 0.797) between HI and HV. However, magnitude-based inference (MBI) analysis indicated that peak force was possibly decreased at 30P following HI and that reactive agility was likely negatively impacted at IP following HV. Friedman analysis indicated a significant decline (p = 0.035) in delayed memory during HV at IP and 30P. Conclusions Results of this study indicate that participants engaging in HV resistance training are more susceptible to experiencing performance declines in reaction time and cognitive function than HI training. These findings shed light on differences in physical and cognitive function recovery from HI and HV training programs.